A SYSTEMATIC LITERATURE REVIEW ON SECURITY ISSUES IN CLOUD COMPUTING USING EDGE COMPUTING AND BLOCKCHAIN: THREAT, MITIGATION, AND FUTURE TRENDS - Khan, Muzammil Ahmad; Shariq Mahmood Khan ,; Siva Kumar Subramaniam, (Malaysian Journal of Computer Science, 2023)
This Systematic Literature Review (SLR) examines the security threats experienced by cloud computing along with QoS by edge computing and scheduling. Various consumers and cloud service providers (CSP) obtained benefits from the cloud computing environment. However, various privacy and security challenges occur in this digital age. This SLR mainly aims to review the state of the art research studies on secure cloud computing with high QoS and its challenges. We examined numerous research studies related to cloud computing security with secure service level agreement (SLA) which are published between 2019 to 2022 from the reputed electronic databases. Cloud computing security is ensured mostly based on trust evaluation, implementation of blockchain technology, authentication, and cryptography techniques, and implementing edge computing in the cloud environment. This SLR also analyzed the research gaps of the previous research papers and provides future research directions to obtain secure cloud computing environment with high QoS performance.